Perforating necrobiosis lipoidica in an old surgical scar - Maria Relvas; Francisca Morgado; José C. Cardoso; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Necrobiosis lipoidica (NL) is an idiopathic granulomatous disease, frequently associated with diabetes mellitus. Histologically, it is characterized by palisaded granulomas involving the deep dermis, but the epidermis is usually spared. We describe a case of perforating NL (PNL), a rare variant of NL, occurring in an atypical location-an old surgical scar on the elbow-in a 70-year-old, non-diabetic, female patient. Histopathological examination of a skin biopsy demonstrated a palisading granulomatous infiltrate involving the full dermis, with an area of epidermal invagination and transepithelial elimination of necrotic material. Clinically, the particularity of PNL is the presence of multiple hyperkeratotic plugs or plaques, within a typical lesion of NL, which correspond to the necrobiotic material being eliminated through the epidermis. Treatment of PNL is still challenging, mainly due to its rarity. Our patient was treated with clobetasol propionate ointment 0.05% one daily, with significant improvement.